Portal Interventions in Liver Transplant Recipients - Saad, Wael E. A. (Seminars in Interventional Radiology, 2012)
Portal vein interventions in liver transplant recipients represent a group of interventions in the management of several disease entities including portal vein stenosis, portal vein thrombosis, and recurrent liver cirrhosis with portal hypertension with and without gastric varices. The procedures performed in these patient populations include portal vein angioplasty with or without stent placement for portal vein stenosis, portal vein thrombolysis with or without stent placement for portal vein thrombosis, transjugular intrahepatic portosystemic shunts or splenic embolization for cirrhosis, and balloon-occluded retrograde transvenous obliteration for gastric varices. This article discusses these disease entities and the minimal invasive procedures used in their management.
Keywords: transplant; liver; vascular complications; endovascular; portal; portal hypertension; TIPS; BRTO